Overall survival of patients with non-small cell lung cancer after surgery treatment - Lončarević, Olivera; Aćimović, Slobodan; Vuković, Jelena; Stojisavljević, Marko; Marić, Nebojša; Lončarević, Slobodan; Petrović, Marina; Milivojević, Ivana; Ignjić, Gordana; Milić, Gordana; Mirilo, Leonida; Rančić, Nemanja (Vojnosanitetski pregled, 2021)
Background/Aim. Lung cancer is one of the most common malignant tumors. About 80% of all lung cancers are non-small cell lung cancer (NSCLC). According to histopathological characteristics, the most common types of NSCLC are squamous cell carcinoma and adenocarcinoma. The aim of this study was to evaluate the overall survival rate in the NSCLC patients initially received surgery according to its histopathological type and T – primary tumor, N –regional lymph nodes, M – distant metastasis (TNM) stages which were treated with surgical treatment, and after that, according to the TNM stage, chemotherapy protocols and/or radiation therapy. Methods. This retrospective case series study included all patients with NSCLC admitted to the Military Medical Academy in Belgrade in the period 2010–2015. A total number of selected patients was 85 (27 females and 58 males). Results. Out of 41 patients with squamous cell carcinoma, 19.5% deceased. On the other hand, in the group of patients with adenocarcinoma, 43.2% out of 44 patients deceased. The average cumulative survival was statistically significantly lower in the adenocarcinoma patients in comparison to the patients with squamous cell carcinoma (1,605.2 vs.1,304.8 days; p = 0.005). On the other hand, the average cumulative survival was statistically significantly lower in our patients in the recurrence group with adenocarcinoma in comparison to the recurrence group with squamous cell carcinoma (1,212.8 vs. 1,835.5 days; p = 0.032). Conclusion. Adenocarcinoma is more aggressive cancer in comparing to squamous cell carcinoma with lower overall survival in comparing to squamous cell carcinoma. Additional studies are needed to identify risk factors for recurrence after surgery, and to additionally explain role of tumor markers and molecular biological techniques in the progression of this kind of cancer.
Keywords: carcinoma, non-small-cell lung; adenocarcinoma; squamous cell carcinoma; survival; recurrence.